Whose Sidewalk? - Kouros, Theodoros (My University, 2021)
Home is a nodal point in a series of polarities, including family-community; space-place; inside-outside; private-public; domestic-social. These may not be stable but seem both solidified and undermined as they play out their meaning and practice in and through the home. The “public” is traditionally the state’s domain, while the “private” the citizens’. But where does “private” end and “public” begin? Can a border or boundary be placed between the two? Is such a boundary culture-specific or universal? Is it static or dynamic? Scholars often perceive borders as barriers and bridges, porous and impenetrable, and border studies have shown that urban entities have their own internal and external borders. I argue that such internal urban micro-boundaries can be found in the domain of domestic space, separating the private from the public, and that they are dynamic and constantly negotiated. Not necessarily marked, they are acknowledged by a mutual and tacit agreement, a social and cultural consensus. In this paper, I focus on common expansions of private into public space in Limassol, Cyprus, and the ways in which, this social consensus is achieved through the use of several tactics. As I illustrate, all these tactics seem to transform public space into private, on a symbolic level. The paper’s contribution lies in the examination of this type of boundary, which has received little academic attention, as well as in the introduction of the term “tactics of inhibition.”
Keywords: Tactics of inhibition; Symbolic boundaries; Domestic space; Urban sidewalk; Cyprus